What is grievance thinking and how can we measure this in sexual offenders? - Barnett, Georgia D. (Legal and criminological psychology, 2011)
Purpose. This study proposes and examines a three-stage model of the grievance process, one of the dynamic risk factors related to risk of sexual recidivism, and aims to evaluate some of the existing measures of this construct. Methods. The research used a sample of 322 male sexual offenders who had completed a cognitive-behavioural programme that aims to reduce recidivism in higher-risk sexual offenders (as measured using a static actuarial tool). Participants completed two questionnaires measuring aspects of grievance thinking pre- and post-treatment. Results. The results indicated some support for stages 1 and 2 of the proposed model. Contrary to the study hypotheses, results indicated that both measures used have similar psychometric properties. Pre- to post-change analyses suggest that the custodial treatment programme may be having some effect on grievance thinking. However, generally offenders' scores on both measures were low pre- and post-treatment and as a result, according to individual change analyses, the majority did not demonstrate reliable or clinically significant change. Those who were classed as high scorers on either measure did, however, demonstrate such change. Conclusions. Further exploration of a three-stage model of grievance is warranted. It appears that current measures of grievance in sexual offenders are not adequate to capture this concept fully.